Gender and dynamic agency: Theory and evidence on the compensation of top executives - Stefania Albanesi; Claudia Olivetti; María José Prados (Federal Reserve Bank of New York, 2015)
We document three new facts about gender differences in executive compensation. First, female executives receive a lower share of incentive pay in total compensation relative to males. This difference accounts for 93 percent of the gender gap in total pay. Second, the compensation of female executives displays lower pay-performance sensitivity. A 1 million increase in firm value generates a 17,150 increase in firm-specific wealth for male executives and a 1,670 increase for females. Third, female executives are more exposed to bad firm performance and less exposed to good firm performance relative to male executives. We find no link between firm performance and the gender of top executives. We discuss evidence on differences in preferences and the cost of managerial effort by gender and examine the resulting predictions for the structure of compensation. We consider two paradigms for the pay-setting process, the efficient contracting model and the "managerial power" or skimming view. The efficient contracting model can explain the first two facts. Only the skimming view is consistent with the third fact. This suggests that the gender differentials in executive compensation may be inefficient.
Keywords: G3; J16; J31; J33; M12; 330; gender differences in executive pay; incentive pay; pay-performance sensitivity